Comparison of O-polysaccharide and hemolysin co-regulated protein as target antigens for serodiagnosis of melioidosis. - Pumpuang, A; Dunachie, S; Phokrai, P; Jenjaroen, K; Sintiprungrat, K; Boonsilp, S; Brett, P; Burtnick, M; Chantratita, N (Public Library of Science, 2017)
Background Melioidosis is a severe disease caused by Burkholderia pseudomallei. Clinical manifestations are diverse and acute infections require immediate treatment with effective antibiotics. While culture is the current diagnostic standard, it is time-consuming and has low sensitivity. In endemic areas, inaccessibility to biosafety level 3 facilities and a lack of good serodiagnostic tools can impede diagnosis and disease surveillance. Recent studies have suggested that O-polysaccharide (OPS) and hemolysin co-regulated protein 1 (Hcp1) are promising target antigens for serodiagnosis of melioidosis. Methodology/Principle findings We evaluated rapid ELISAs using crude antigens, purified OPS and Hcp1 to measure antibody levels in three sets of sera: (i) 419 serum samples from melioidosis patients, Thai and U.S. healthy donors, (ii) 120 serum samples from patients with other bacterial infections, and (iii) 423 serum samples from 200 melioidosis patients obtained upon admission and at 12 and 52 weeks post-recovery. We observed significantly higher antibody levels using the crude antigen prepared from wild type B. pseudomallei K96243 compared to that of an OPS-mutant. The areas under receiver operator characteristics (AUROCCs) for diagnosis were compared for individual Hcp1-ELISA or OPS-ELISA or combined Hcp1/OPS-ELISA. For Thai donors, AUROCCs were highest and comparable between the Hcp1-ELISA and the combined Hcp1/OPS-ELISA (0.95 versus 0.94). For U.S. donors, the AUROCC was highest for the combined Hcp1/OPS-ELISA (0.96). Significantly higher seropositivity was observed in diabetic patients compared to those without diabetes for both the Hcp1-ELISA (87.3% versus 69.7%) and OPS-ELISA (88.1% versus 60.6%). Although antibody levels for Hcp1 were highest upon admission, the titers declined by week 52 post-recovery. Conclusions/Significance Hcp1 and OPS are promising candidates for serodiagnosis of melioidosis in different groups of patients. The Hcp1-ELISA performed better than the OPS-ELISA in endemic areas, thus, Hcp1 represents a promising target antigen for the development of POC tests for acute melioidosis.